PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN MEDIA WORDWALL UNTUK MENINGKATKAN HASIL BELAJAR SISWA TENTANG MATERI SIKAP DAN PERILAKU MENJAGA LINGKUNGAN SEKITAR DI KELAS II SD NEGERI NAIKOTEN I - Terenci Maria Mawa; Lolang Maria Masi; Netty E. A. Nawa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
A thesis by Terenci Maria Mawa, Student ID Number 2101140174, entitled "TheApplication of Problem-Based Learning Models with Wordwall Media to ImproveStudent Learning Outcomes on Environmental Attitudes and Behavior in Grade II ofNaikoten 1 Public Elementary School." The research question is how to applyproblem-based learning models with wordwall media to improve student learningoutcomes on environmental attitudes and behavior in grade II of Naikoten 1 PublicElementary School. The purpose of this study was to improve student learningoutcomes on Environmental Attitudes and Behavior through the application ofProblem-Based Learning (PBL) models with wordwall media in grade II of Naikoten1 Public Elementary School. This study was a Classroom Action Research (CAR)conducted in two cycles. Each cycle consisted of planning, implementation,observation and evaluation, and reflection. Twenty-eight students participated,comprising 15 boys and 13 girls. Data collection techniques used observationsheets and learning outcome evaluation tests. The results showed an increase instudent learning outcomes from cycle I to cycle II. In Cycle I, 18 students (64.28%)achieved learning mastery, while 10 students (35.72%) did not. After improvementsin Cycle II, the number of students achieving learning mastery increased to 25(89.28%). Based on the research results above, it can be concluded that theapplication of the problem-based learning model assisted by wordwall media caneffectively improve student learning outcomes in the material on Attitudes andBehavior in Protecting the Environment in class II of Naikoten 1 Public ElementarySchool.